2021
DOI: 10.1093/ornithapp/duab054
|View full text |Cite
|
Sign up to set email alerts
|

N-mixture models estimate abundance reliably: A field test on Marsh Tit using time-for-space substitution

Abstract: Imperfect detection in field studies on animal abundance, including birds, is common and can be corrected for in various ways. The binomial N-mixture (hereafter binmix) model developed for this task is widely used in ecological studies owing to its simplicity: it requires replicated count results as the input. However, it may overestimate abundance and be sensitive to even small violations of its assumptions. We used a 33-year dataset on the Marsh Tit (Poecile palustris), a sedentary forest passerine, from Bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Population density has been estimated for other marsh birds (e.g., Harms and Dinsmore 2012, Wiest et al 2016, 2019, Vanausdall et al 2022) despite the high potential for these oftensecretive species to remain undetected at or immediately adjacent to the observer, which is a violation of a distance sampling assumption (Buckland et al 1993). N-mixture models can produce reliable population density estimates via repeated surveys at locations, though are known to overestimate population size where densities are low (Neubauer et al 2022), as is often true for King Rails. By using a correction factor, a distance sampling approach could feasibly yield an accurate King Rail population density estimate without employing the double-observer method (Thomas et al 2010), similar to approaches used for taxa such as cetaceans (e.g., Andriolo et al 2006) that often remain undetected at or immediately adjacent to an observer.…”
Section: Discussionmentioning
confidence: 99%
“…Population density has been estimated for other marsh birds (e.g., Harms and Dinsmore 2012, Wiest et al 2016, 2019, Vanausdall et al 2022) despite the high potential for these oftensecretive species to remain undetected at or immediately adjacent to the observer, which is a violation of a distance sampling assumption (Buckland et al 1993). N-mixture models can produce reliable population density estimates via repeated surveys at locations, though are known to overestimate population size where densities are low (Neubauer et al 2022), as is often true for King Rails. By using a correction factor, a distance sampling approach could feasibly yield an accurate King Rail population density estimate without employing the double-observer method (Thomas et al 2010), similar to approaches used for taxa such as cetaceans (e.g., Andriolo et al 2006) that often remain undetected at or immediately adjacent to an observer.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found limitations with N‐mixture models (Barker et al 2017, Link et al 2018), which show that small violations can lead to large biases in estimation. Recently, Neubauer et al (2022) found that the strength and direction of these biases in abundance estimation depend upon the presence of unmodeled heterogeneity in detection probability, which is more severe with low detection probability. It is probable that our research, given the low detection probability, has some abundance estimation bias.…”
Section: Discussionmentioning
confidence: 99%
“…N‐mixture models allow for the estimation of abundance (λ) and detection probability (p $p$) without the explicit identification of individuals within the population. While some studies have found limitations of N‐mixture models (Barker et al 2017, Link et al 2018), other recent work suggests that these models are a valid alternative to intensive population monitoring for abundance estimation (Keever et al 2017, Kidwai et al 2019, Neubauer et al 2022). We combined counts of spring salamanders in each stream location, regardless of method (added counts across methods [LLB, VES, FS] for each UPS, DS1, and DS2 location, which includes 3 separate counts of abundance) for all 11 streams.…”
Section: Methodsmentioning
confidence: 99%
“…The model also enabled us to include environmental metrics as covariates; therefore both parameters (abundance and detection) could be expressed as functions of environmental covariates through a log or logit link, respectively. Previous studies have demonstrated that N-mixture models offer reliable estimates of abundance aligning with outcomes from alternative methods such as capturemark-recaptures (Ficetola et al 2018;Neubauer et al 2022).…”
Section: Statistical Analysesmentioning
confidence: 99%